Exploratory Analysis of Operational Thermal Behavior in Electric Bus Batteries: A Diagnostic Perspective - Gaybor, Miguel A.; Ullon, Hernan R.; de Almeida, Madon C. (Anais do Workshop Latinoamericano de Dependabilidade e Segurança em Sistemas Veiculares (SSV); 2024: Anais do I Workshop Latinoamericano de Dependabilidade e Segurança em Sistemas Veiculares, 2024)
This paper presents an analysis of the thermal behavior of electric bus batteries, emphasizing diagnostic techniques to identify potential issues in the Battery Thermal Management System (BTMS). Using real-time data from a CAN interface reader, the study focuses on temperature fluctuations and patterns that pose risks to the BTMS. Key findings include instances where maximum cell temperatures exceed safe operational limits, indicating a decline in BTMS effectiveness over time. The research also highlights the importance of monitoring the temperature difference (ΔT) between cells to ensure thermal distribution efficiency. Given the often limited data provided by electric vehicle manufacturers, this methodology demonstrates that early signs of thermal anomalies can be detected, offering valuable insights for improving maintenance strategies and ensuring the safety and longevity of electric bus batteries, particularly in climates where thermal management is crucial.